The Effect of Digital Culture on Employee Performance: A Conceptual Paper - Alfayza Diva Azra; R. Nurafni Rubiyanti; Anita Silvianita; Arry Widodo (International Journal of Scientific Multidisciplinary Research, 2024)
Successful digital transformation in an organization is supported by a digital culture. The aim of this study is to determine the influence of digital culture in the organization on the performance of employees at the Main Branch Office of PT Pos Indonesia Bandung. The quantitative method used in this research is simple linear regression analysis techniques and descriptive analysis. This paper is framed as a concept paper. A comprehensive literature review and previous research were used as the main research tools. This study shows that digital culture has a positive effect on employee performance. A digital culture that increases employee awareness and participation in digital transformation can increase employee capabilities in providing more effective and efficient service quality